Linking Green Accounting and CSR Practices to Financial and Sustainability Performance - Kusuma Wardani, Ratri; Riadi, Sugeng (Journal of Applied Accounting and Taxation, 2025)
During the global pressure for environmental transparency, green accounting and CSR becomes a bridge between company’s profitability and sustainability. This research examines the influence of green accounting and CSR on financial performance and sustainability performance. PLS-SEM method with SmartPLS 4.1.2 would be used to analyze the data for this study. Samples used in this study consisted of 39 companies from mining and crude palm oil sectors listed on Indonesia Stock Exchange (IDX) between 2021-2023. Green accounting will be measured with PROPER awards. CSR will be measured based on environmental costs. Financial performance will be measured using ratio of Return of Assets (ROA), and sustainability performance will be measured with GRI 2021 index. Analysis results indicate that green accounting negatively impacts financial performance, but exerts a significant positive influence on sustainability performance. CSR positively enhances financial performance but has no significant effect on sustainability performance. Moreover, analysis confirms no mediating role of financial performance in the connections linking green accounting or CSR to sustainability performance.